PERSEPSI PEMANGKU KEPENTINGAN TERHADAP PENGELOLAAN LANSKAP HUTAN DAS WAE BATU MERAH KOTA AMBON - Siahaya, Jesy Sammy; Latuamury, Bokiraiya; Loppies, Ronny (Jurnal Nusa Sylva, 2024)
Forest landscape management in the Wae Batu Merah Watershed (DAS) in Ambon City is a complex and urgent issue, given its strategic role in maintaining ecosystem balance, reducing natural disaster risks, and supporting the sustainability of natural resources for local communities. Forests in this watershed protect ecosystems from erosion and soil degradation and provide critical ecosystem services, such as clean water sources and biodiversity habitats. However, pressures from human activities, such as land-use changes, urbanization, and poorly planned management practices, have threatened the sustainability of forest landscape functions in this area. This study explores stakeholders' views and perceptions regarding forest landscape management in the Wae Batu Merah Watershed, Ambon City. This research employs in-depth interviews and field observations involving key stakeholders, such as the Forestry Department, the Provincial Forestry Technical Unit (UPTD) of Maluku, and the communities of Batu Merah and Soya villages. The results reveal that stakeholders’ perceptions of forest landscape management in the Wae Batu Merah Watershed fall within the moderate category regarding knowledge, understanding, and attitudes. These perceptions vary from full support to rejection. Support is generally associated with initiatives actively involving stakeholders and providing tangible benefits. Conversely, rejection arises when policies or management practices are perceived as harmful or insufficiently inclusive. These findings underscore the importance of collaborative and inclusive approaches to forest landscape management to achieve ecological and social sustainability in the Wae Batu Merah Watershed.